Comparative Study on Blood Protein Polymorphism of Captive Bali Starling (Leucospar Rotschildi) from Indonesia, the United States and England - Machmud Thohari; Burhanuddin Masyud; Sri Soepraptini Mansjoer; Cece Somantri; EKS Harini Muntasib; Agus Hikmat (Media Konservasi, 1991)
Bali Starling (Leucopsar rotschildi) is stated as endangered species, and protected by law since 1970. The bird is only found in Bali Barat National Park. Captive breeding program of the bird has been camed out successfully in Indonesia, the United States and England. Furthermore, the individuals were planned released into their natural habitats. Therefore, a genetical study is important to know the genetical variability among the populations. Research on genetic polymorphism was conducted using an electrophoresis technique. Three captive populations of Bali starling and two other starling species i.e., black-winged starling (Smcnus n~elanopteros) and Asian pied starling(S. confra)were used for the study. All individualsof Bali  starlingwere from Surabaya Zoo, consist of six individuals bred in Indonesia, eight individuals bred in the United States, and three individuals bred in England. Three individuals of black-winged starling and two individuals of Asian pied starling were bought from bird market at Bogor. Four locus analysed, i.e. Transferine (T), Post Transferine-1 (FT-I), Post Transferine-2 (FT-2) and Albumine (Al). The electrophoresis analysis resulted that all individuals of Bali starling were homozygote. So, there was no genetical polymorphism found among the Bali starling populations. The black-winged starling and Asian pied starling shown some degree of polymorphism, with heterozygosity value of 0.141 and 0.125 respectively. The study concluded that the heterozygotic rate of the captive Bali starling was extremely very low. The phenomenon shown that the genetical status of the Bali starling is extremely in critical quality. This maybe as a consequenq of the captive breeding by using only a small populations. Further research should be continued to analyse other loci, involving the natural populations of theBali starling.